2012
DOI: 10.1364/oe.20.00a932
|View full text |Cite
|
Sign up to set email alerts
|

White organic light emitting diodes with enhanced internal and external outcoupling for ultra-efficient light extraction and Lambertian emission

Abstract: White organic light emitting diodes (WOLEDs) suffer from poor outcoupling efficiencies. The use of Bragg-gratings to enhance the outcoupling efficiency is very promising for light extraction in OLEDs, but such periodic structures can lead to angular or spectral dependencies in the devices. Here we present a method which combines highly efficient outcoupling by a TiO 2 -Bragg-grating leading to a 104% efficiency enhancement and an additional high quality microlens diffusor at the substrate/air interface. With t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The waveguided light confined in the active organic and ITO layers comprises 40–60% of the total emission. To further extract the waveguided light confined within high‐refractive‐index organic and ITO anode regions (waveguide modes), various strategies to engineer substrates have been proposed . The method based on a high‐refractive‐index substrate has been demonstrated to be highly effective, and can remarkably increase the amount of waveguided light coupled from the ITO/organic layers into the substrate .…”
Section: Flexible Photonic Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The waveguided light confined in the active organic and ITO layers comprises 40–60% of the total emission. To further extract the waveguided light confined within high‐refractive‐index organic and ITO anode regions (waveguide modes), various strategies to engineer substrates have been proposed . The method based on a high‐refractive‐index substrate has been demonstrated to be highly effective, and can remarkably increase the amount of waveguided light coupled from the ITO/organic layers into the substrate .…”
Section: Flexible Photonic Devicesmentioning
confidence: 99%
“…Instead of using high‐refractive‐index substrates, the extraction of the waveguided light can be realized by implementing internal extraction structures, such as optical gratings or photonic crystals between the substrate and the transparent electrode . Most recently, Qu et al demonstrated a method for extracting the waveguided light of OLEDs by inserting a planar, non‐diffractive, dielectric grid layer between the transparent ITO electrode and the substrate .…”
Section: Flexible Photonic Devicesmentioning
confidence: 99%
“…Previous studies have shown that η OC of conventional OLEDs is limited at about 20% because total reflection at internal interfaces that light incidents from high refractive index medium to low refractive index medium 11‐13 . The η OC of OLEDs with various light‐out‐coupling (LOC) layers has been already reported 14‐25 . But there is still room for improvement because the η OC of OLEDs is only 30–50%.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The η OC of OLEDs with various light-out-coupling (LOC) layers has been already reported. [14][15][16][17][18][19][20][21][22][23][24][25] But there is still room for improvement because the η OC of OLEDs is only 30-50%. Simulation methods for the design of a white OLED (WOLED) structure with a LOC layer are indispensable to improve η OC .…”
Section: Introductionmentioning
confidence: 99%
“…To extract the waveguided light, internal outcoupling structures can be categorized into two groups. One is to modulate the photon states to extract light via optical gratings or photonic crystals 10,11 . This method leads to emission properties that depend on both viewing angle and wavelength, making it incompatible with display and lighting applications.…”
mentioning
confidence: 99%